Gaya Kepemimpinan Visioner Kepala Sekolah Dalam Meningkatkan Kinerja Guru di Mts Ylpi Ibaadurrahman Kota Sukabumi - Abdul Fajar; Mulyawan Safwandy Nugraha (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
Abstract with "School Principal's Visionary Leadership Style in Improving Teacher Performance at Mts Ylpi Ibaadurrahman Sukabumi City". The main problems are: 1) What is the leadership style of the principal at Mts Ylpi Ibaadurrahman, Sukabumi City? 2) What are the implications for the performance of teaching staff at Mts Ylpi Ibaadurrahman, Sukabumi City? 3) How does the school principal transform the school's vision and mission in improving the quality of education at Mts Ylpi Ibaadurrahman, Sukabumi City? The research method used is a qualitative research method, data collection techniques used are through observation, interviews, and documentation. While the objectives to be achieved are to determine the leadership style of the visionary principal at Mts Ylpi Ibaadurrahman Sukabumi City and to find out the implications for the performance of educational staff at Mts Ylpi Ibaadurrahman Sukabumi City. The results of this study indicate that the principal's leadership style applied by the principal is generally responded to by good cooperation by his subordinates, who use a democratic-participatory leadership style. With this leadership that has an impact on educational staff because of democratic leadership the freedom to develop potential is enormous, good working relationships are established between superiors and subordinates, creating a comfortable work environment and understanding how important it is to invite all school parties to realize this vision in accordance with their duties and responsibilities. each. Thus the author can conclude that in this study principals are generally carried out with the cooperation of leaders and their members and how a leader motivates morale, fosters discipline, shows exemplary attitudes and behavior that school principal leadership in improving the performance of educational staff greatly contributes which is good for the progress of the quality of learning so that it can encourage the quality of education where the performance of educators and education staff is the key to success in the world of education. Research implication: The author suggests that the Principal maintains the main duties and functions of leadership that have been well developed, and continuously improves educational performance according to the needs of the institution and maintains time discipline and responsibility with each task as planned by the institution and prosper educators by carrying out assignments according to their respective pokies.